Estimating the policy rule from money market rates when target rate changes are lumpy - Jean-Sébastien Fontaine (Bank of Canada, 2012)
Most central banks effect changes to their target or policy rate in discrete increments (e.g., multiples of 0.25%) following public announcements on scheduled dates. Still, for most applications, researchers rely on the assumption that the policy rate changes linearly with economic conditions and they do not distinguish between dates with and without scheduled announcements. This assumption is not innocuous when estimating the policy rule based on daily frequency. For the 1994-2011 period, and using an otherwise standard term structure model, I find that accounting for discrete changes leads to economically different estimates. Only the model based on discrete changes depicts a picture that is consistent with existing evidence on the monetary policy rule and risk premium. I study the information content of key policy announcements in the period from the end of 2008, where the policy rate reached a lower bound in the US, until the end of 2011.
Keywords: E43; E44; E47; G12; G13; 330; Asset pricing; Financial markets; Interest rates